A Behavioristic Approach to Classroom Management in Islamic Cultural History (SKI) Learning - Aulia, Risma; Ikri Matusaadah; Yudril Basith; Hayaturrohman; Agustini Diah Pancawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2026)
This study aims to analyze the implementation of a behavioristic approach in classroom management in the subject of Islamic Cultural History (SKI) and to identify the supporting and inhibiting factors in its implementation. The behavioristic approach emphasizes the formation of learning behavior through planned stimulus, response, and reinforcement mechanisms.This research employed a qualitative descriptive approach. Data were collected through in-depth interviews and observations involving the SKI teacher and Grade VII students at SMPIT Darul Muttaqien Parung, Bogor Regency. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing, and was validated through technique triangulation. The findings indicate that the behavioristic approach is implemented through academic, material, and psychological stimuli, as well as reinforcement in the form of rewards and educative consequences. This implementation contributes to the development of students’ discipline, activeness, and responsibility. However, the behavioristic approach is not applied mechanically, but is adapted through the integration of Islamic values, thus supporting not only observable behavior but also the process of value internalization. Supporting factors include teacher consistency, positive reinforcement, and the contextualization of learning materials. In contrast, inhibiting factors include students’ perceptions, differences in individual characteristics, and limited instructional time. Therefore, the behavioristic approach contributes to shaping learning behavior and needs to be complemented with other approaches to support deeper value internalization.